Effect of argon ion bombardment on amorphous silicon carbonitride films - Batocki, R. G. S. [UNESP]; Mota, R. P. [UNESP]; Honda, R. Y. [UNESP]; Santos, D. C. R.; Aguiar, J. A.; Vargas, CAP; Tellez, DALN; Bohorquez, LTC; Shanenko, A.; Jardim, R. F.; Peeters, F. (Iop Publishing Ltd, 2014)
Amorphous silicon carbonitride (a-SiCN:H) films were synthesized by radiofrequency (RF) Plasma Enhanced Vapor Chemical Deposition (PECVD) using hexamethyldisilazane (HMDSN) as precursor compound. Then, the films were post-treated by Plasma Immersion Ion Implantation (PIII) in argon atmosphere from 15 to 60 min The hardness of the film enhanced after ion implantation, and the sample treated at 45 min process showed hardness greater than sixfold that of the untreated sample. This result is explained by the crosslinking and densification of the structure Films were exposed to oxygen plasma for determining of the etching rate. It decreased monotonically from 33 angstrom/min to 19 angstrom/min for the range of process time, confirming structural alterations. Hydrophobic character of the a-SiCN:H films were modified immediately after ion bombardment, due to incorporation of polar groups. However, the high wettability of the films acquired by the ion implantation was diminished after aging in air. Therefore, argon PIII made a-SiCN.H films mechanically more resistant and altered their hydrophobic character.